Effect of microwave power on energy gap of ZnO nanoparticles synthesized by microwaving through aqueous solutions - Promnopas,W. (Academic Press Inc., 2015)
© 2014 Elsevier Ltd. All rights reserved. Hexagonal wurtzite ZnO nanoparticles were successfully synthesized in aqueous solutions containing zinc acetate (Zn(OAc)2) and sodium hydroxide (NaOH) by microwaving at 400, 600 and 800 W for 6 min. The as-synthesized products analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Raman spectroscopy were pure hexagonal wurtzite ZnO nanostructure with sharp and strong optical phonon Raman-active mode of E2H at 438.7 cm-1 and in the shape of nanoparticles clustered together as nanoplate-nanorod mixture with different orientations. The central photoluminescence (PL) emission was detected at 378.9-382.4 nm of UV region, due to the recombination of excitons. The energy band gap of the as-synthesized products characterized by UV-visible absorption spectroscopy was decreased form 3.20 eV to 3.01 eV by increasing in the microwaving power from 400 W to 800 W, due to the decreasing in the full width at half maximum (FWHM) of the XRD main peaks and the improvement of crystalline degree of the products.